Community-Onset Bacterial Coinfection in Children Critically Ill With Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (6th March 2023) - Moffitt, Kristin L; Nakamura, Mari M; Young, Cameron C; Newhams, Margaret M; Halasa, Natasha B; Reed, J Nelson; Fitzgerald, Julie C; Spinella, Philip C; Soma, Vijaya L; Walker, Tracie C; Loftis, Laura L; Maddux, Aline B; et al.
Abstract: Background: Community-onset bacterial coinfection in adults hospitalized with coronavirus disease 2019 (COVID-19) is reportedly uncommon, though empiric antibiotic use has been high. However, data regarding empiric antibiotic use and bacterial coinfection in children with critical illness from COVID-19 are scarce. Methods: We evaluated children and adolescents aged <19 years admitted to a pediatric intensive care or high-acuity unit for COVID-19 between March and December 2020. Based on qualifying microbiology results from the first 3 days of admission, we adjudicated whether patients had community-onset bacterial coinfection. We compared demographic and clinical characteristics of those who did and did not (1) receive antibiotics and (2) have bacterial coinfection early in admission. Using Poisson regression models, we assessed factors associated with these outcomes. Results: Of the 532 patients, 63.3% received empiric antibiotics, but only 7.1% had bacterial coinfection, and only 3.0% had respiratory bacterial coinfection. In multivariable analyses, empiric antibiotics were more likely to be prescribed for immunocompromised patients (adjusted relative risk [aRR], 1.34 [95% confidence interval CI, 1.01–1.79]), those requiring any respiratory support except mechanical ventilation (aRR, 1.41 [95% CI, 1.05–1.90]), or those requiring invasive mechanical ventilation (aRR, 1.83 [95% CI, 1.36–2.47]) (compared with no respiratory support). The presence of a pulmonary comorbidity other than asthma (aRR, 2.31 [95% CI, 1.15–4.62]) was associated with bacterial coinfection. Conclusions: Community-onset bacterial coinfection in children with critical COVID-19 is infrequent, but empiric antibiotics are commonly prescribed. These findings inform antimicrobial use and support rapid de-escalation when evaluation shows coinfection is unlikely. Abstract : The majority of US children admitted to intensive care for COVID-19 received empiric antibiotics. Community-onset bacterial coinfection was infrequent but increased with the degree of organ dysfunction, and was more common in patients with underlying nonasthma lung disease.